ABO blood group genotypes, plasma von Willebrand factor levels and loading of von Willebrand factor with A and B antigens - Morelli, Vania M.; de Visser, Marieke C. H.; van Tilburg, Nico H.; Vos, Hans L.; Eikenboom, Jeroen C. J.; Rosendaal, Frits R.; Bertina, Rogier M. (Thrombosis and Haemostasis, 2007)
ABO blood group is a genetic determinant of von Willebrand factor (VWF) levels. We investigated the effect of ABO genotypes on VWF and factor VIII (FVIII) levels and on the degree to which VWF is loaded with A- and B-antigens, expressed as normalized ratios, nA-ratio and nB-ratio, respectively, in the Leiden Thrombophilia Study, a large case-control study on venous thrombosis. We found that the ABO locus had an allele-specific, dosage dependent effect on VWF and FVIII levels and on the loading of VWF with A-antigen and B-antigen. The highest mean nA- and nB-ratios were found in A1A1 and BB genotypes, respectively. Four A1 O carriers had four 43-bp repeats in the minisatellite region of theABO gene in stead of the expected one repeat. All had a reduced nA-ratio compared to A 1 O carriers with one repeat in their A1 allele. The amount of A – and B- antigens expressed onVWF (nA-ratio and nB-ratio) explained about 18% (R2) of the variation in VWF levels.
Keywords: ABO genotypes; von Willebrand factor; A and B antiens